Supermassive black holes coalescence mediated by massive perturbers: implications for gravitational waves emission and nuclear cluster formation - Arca Sedda, Manuel; Berczik, Peter; Spurzem, Rainer (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. A large fraction of galactic nuclei is expected to host supermassive black hole binaries (BHB), likely formed during the early phase of galaxies asse